Identfikasi Hama Kutudaun pada Tanaman Cabai di Indralaya - Edo Farhan; Famita Dewi; May Shintya Simbolon; Sri Rahayu Ningsih; Zahrotun Nisa Yusuf; Chandra Irsan (Seminar Nasional Lahan Suboptimal, 2021)
Farhan E, Famita D, Simbolon MS, Ningsih SR, Yusuf ZN, Irsan C.  2021. Identification of aphids on chili plants in Indralaya. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 530-536.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Chili (Capsicum frutescens sp.)is a type of plant organiting from the Americas. Chili plants in Indonesia are reported to have been attacked by many diseases caused by insect such as aphids. The research was conducted in Tanjung Pering, North Indralaya District, Ogan Ilir, and Indralaya Indah District , Indralaya District, Ogan Ilir District, South Sumatra. The purpose of this research was to indentify the characteristics of chilli crop  and to know the influence of the population of aphids on Chili with different location and treatment. The method used in making this scientific paper were literature study and observation. The results showed that the plants in Indralaya Indah location (land B) more pest aphids than in Tanjung Pering (land A). On land A there was pest of species aphids (Myzus persicae). On land B there were aphid pests of Aphis gossypii species, Myzus persiciae, and whitefly pest Bemisia tabacispecies. In conclusion, the presence oh whitefly population on land A is caused by the presence of papaya plants around the land. Aphid pests attack  many chili plants in land B because the amount of weeds is too high than in land A.